THE EFFECT OF CONSUMER PERCEPTIONS AND LIFESTYLE ON WILLINGNESS TO PAY PREMIUM PRICE WAGYU PRODUCTS - Yuli Kartika Dewi; Jessica Gosal Gosal (Business Management Journal, 2020)
Willingness to pay premium price is the willingness of individuals to spend a greater amount of money with the aim of getting a product or service of higher quality than other products or services. This study conducted a study of the effect of consumer perceptions and lifestyles on the willingness to pay premium prices of Wagyu products. As we know that the price of Wagyu beef is quite high, around Rp. 300,000 - Rp. 850,000 per kilogram depending on the quality. The purpose of this study was to determine: (1) the effect of consumer perceptions on the willingness to pay premium prices of Wagyu products; (2) the influence of lifestyle on the willingness to pay premium price of Wagyu products. The research method used is quantitative research. The population in this study are all consumers who have bought Wagyu meat in different cities with an infinite amount. Sampling in this study used a purposive sampling technique with a total sample of 123 people who had bought Wagyu products. Data collection techniques using a questionnaire with a Likert scale. This study uses multiple regression analysis test as an analytical tool to test hypotheses. Data from the questionnaire were analyzed to test factors and test variables using SPSS 21. The results of this study showed: (1) consumer perceptions had a positive and significant effect on willingness to pay premium prices for Wagyu meat products; (2) lifestyle has a positive and significant effect on the willingness to pay premium prices of Wagyu products.